Estudo químico e atividade antirradicalar da fração acetato de etila das folhas de Actinocephalus divaricatus (Koern.) Sano (Eriocaulaceae) - Souza, Thaís Pezza de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The Eriocaulaceae family has 1.400 species divided into 10 genera, with many plants being endemic in Brazil. One of these genera is the Actinocephalus, which until 2004 was a subsection of the genre Paepalanthus and, because of cladistic studies and morphological analyzes of several species, was elevated to genus Actinocephalus. Therefore this genus currently has 49 species and the specie studied in this work was Actinocephalus divaricatus. The aerial parts of A. divaricatus were separated into scapes, capitula and leaves. A methanolic extract was made with the leaves, and after a partition with wather and ethyl acetate was made and with the aqueous fraction a partition with n-butanol was made. The ethyl acetate fraction was studied, mainly due to its high yield, and then a fractioning in sephadex LH-20 was made. With the obtained fractions was made a TLC, providing the fraction 24 (1,5 mg) that, by presenting only one spot, was analyzed by NMR of 1H, and was identified like 6-hydroxy-7-methoxiquecertin (AdFa1). The fraction 12 (129,5 mg) was also obtained and was purified and separated by HPLC-PDA preparative, resulting in four other substances that, after analysis, were identified like being: 3,4-dihydroxybenzoic acid (AdFa2), p-hydroxybenzoic acid (AdFa3) e 4-hydroxy-3-methoxybenzoic acid (AdFa4) and a flavonoid derivated from quercetin: 6-hydroxy-7-methoxyquercetin-3-O-β-D-glicopyranoside (AdFa5). With AdFa5 was made the quantification by HPLC-PDA, being determined in the sample 25,65 ± 0,43 mg g-1 of flavonoid (AdFa5) in the ethyl acetate fraction. In addition, the antiradicalar test was performed using standard gallic acid, which showed IC50 of 30,69 ± 4,9 μg mL-1, and with the standart quercetin, it showed a IC50 of 50,96 ± 5,6 μg mL-1, while the fraction IC50 was 440,66 ± 24,27 μg mL-1. The total phenol content in the ethyl acetate fraction was 274,61 μg mg-1, while the total flavonoids content was 13,14 μg mg-1 of ethyl...

A família Eriocaulaceae possui 1.400 espécies divididas em 10 gêneros, sendo que muitas plantas são endêmicas ao Brasil. Um desses gêneros é o Actinocephalus, que até 2004 era uma subseção do gênero Paepalanthus e que, devido a estudos cladísticos e análises morfológicas de várias espécies, foi elevado a gênero Actinocephalus. Portanto, atualmente este gênero conta com 49 espécies, sendo Actinocephalus divaricatus a estudada neste trabalho. As partes aéreas de A. divaricatus foram separadas em escapos, capítulos e folhas. Com as folhas foi preparado o extrato metanólico e, posteriormente, foi realizada uma partição com água e acetato de etila e, com a fração aquosa obtida, foi realizada uma partição com n-butanol. A fração acetato de etila, devido principalmente ao seu alto rendimento, foi escolhida para fracionamento em sephadex LH-20. Com as frações obtidas foi realizada CCD, propiciando a fração 24 (1,5 mg) que, por apresentar somente um spot, foi analisada por RMN de 1H, sendo identificada a 6-hidroxi-7-metoxiquecertina (AdFa1). Também foi obtida a fração 12 (129,5 mg), que foi purificada por HPLC-PDA semipreparativo, resultando no isolamento de outras quatro substâncias, que após análise por RMN foram identificadas como sendo: ácido 3,4-diidroxibenzóico (AdFa2), ácido p-hidroxibenzóico (AdFa3) e ácido 4-hidróxi-3-metoxibenzóico (AdFa4) e ao flavonoide 6-hidroxi-7-metoxiquercetina-3-O-β-D-glicopiranosídeo (AdFa5). Com (AdFa5) foi realizada a quantificação por HPLC-PDA, sendo determinado na amostra 25,65 ± 0,43 mg g-1 do flavonoide (AdFa5) na fração acetato de etila. Além disso, foi realizado o ensaio antirradicalar, com os padrões de ácido gálico, que apresentou IC50 = 30,69 ±4,9 μg mL-1 e de quercetina, que apresentou IC50 de 50,96 ±5,6 μg mL-1, enquanto que o IC50 de fração acetato de etila foi de 440,66 ± 24,27 μg mL-1. O teor de fenóis totais na fração acetato de etila...
Keywords: Ácido fenólico; Eriocaulaceae; Metabólitos; Flavonoides; Cromatografia líquida de alta eficiência; Flavonoids